Hubungan Asupan Vitamin C Dan Serat Dengan KadarTrigliserida Pada Pasien Jantung Koroner Di InstalasiRawat Jalan Rsud Dr. Moewardi Surakarta - Erniningsih, Sri, Dwi Sarbini S.ST., M.Kes, Rusjiyanto, SKM., M.Si (2016)
Background :Coronary heart disease (CHD) is a condition where there is accumulation of plaque in coronary blood vessels. It happens due to arteriosclerosis (hardening of the arteries) caused by levels of serum cholesterol and high triglycerides. Non-pharmacological and pharmacological therapies can be used to reduce levels of triglycerides in the blood. Non-pharmacological therapies on the intake of nutrients are vitamin C as an antioxidant and fiber for good metabolism of cholesterol and triglyceride. Based on a preliminary survey at Hospital Dr.Moewardi in June -August 2015 CHD, patient's prevalence increased from 1.42% in June to 1.9% in August. Objective :To assess the correlation between intakes of vitamin c and fiber and triglyceride levels in coronary heart disease outpatienst at Dr. Moewardi hospital, Surakarta. Methods :An observational research with cross-sectional design, with 30 participants who were selected according to the selection criteria (Consecutive Sampling). The participants in this research were patients with coronary heart disease aged 30-65 years.The data on intakes of vitamin C and fiber were obtained through direct interview using the Semi-quantitative Food Frequency Quesionnare (SQFFQ) form and triglyceride levels obtained from medical records and were analyzed using Pearson Product Moment Correlation tests. Result :All subjects had low vitamin C intake. Around 90% of them had low fiber intake. A total of 53.3% of patients with coronary heart disease had normal triglyceride levels. Result of statistical test analysis between vitamin C intake and triglyceride levels obtained p =0.024, while the result of the relationship between fiber intake and triglyceride levels showed p =0.228. Conclussion &Suggest :There was no relationship between fiber intake and triglyceride levels in patients with coronary heart disease at the Dr.Moewardi Hospital. There was a relationship between vitamin C intake and triglyceride levels in patients with coronary heart disease at the Dr.Moewardi Hospital. Performing healthy behavior with regular exercise, paying attention to diet and avoiding stress are important factors to prevent CHD. Keywords : intake of vitamin C, fiber, trgycerides Literatures : 54 (1997-2015)